UPAYA PEMERTAHANAN BAHASA KONE KONE’E (DIALEK TALLUMPANUAE) DI DESA BONDE, CAMPALAGIAN, POLEWALI MANDAR - Asyrah; Noer Jihad Saleh; Herawaty Abbas (JOEL: Journal of Educational and Language Research, 2022)
In this research is discussed about a local language that its existence is not well known, it is Kone’ Kone’e language in Bonde village, Campalagian district, Polewali Mandar region of West Sulawesi. People used to get this language wrong to be known as one of Mandarnese language, whereas this language is part of ancient Buginese language, the seventh dialect. Its existence among the majority language still survive eventhough its speaker is the minority. In this research the aim of the author is toreveal what factors behind the existence of this language to still survive, in this case the author has limited this study in the field of family, neighbourhood, and religion. The method that is used in this research is descriptive qualitative method where gathered all opinion, response, information in the form of description to reveal the problem. In defensing the existence of this language there are some factors such as lexical, demography, language usage pattern, and language attitude in the field of family, neighbourhood ad religion. Whole four factors have been done by the villagers in Bonde, that is why until today this language still survive in the middle of majority language.